Modern Digital Approaches to Diagnosis and Planning of Orthopedic Rehabilitation in Patients with Tooth Loss due to Maxillofacial Injuries (Literature Review) - Brozhyna Б. (Actual Dentistry, 2025)
Topicality. The article addresses the current issue of the unique characteristics of modern digital approaches to diagnosing and planning orthopedic rehabilitation in patients with maxillofacial region injuries resulting in tooth loss. This issue is becoming more urgent as a result of active hostilities in Ukraine and the growing number of military and civilians with injuries to the maxillofacial area. For effective rehabilitation, digital technologies can be used with traditional diagnostic methods. It has been shown that digital approaches and technologies have been actively developing recently, their implementation is becoming more widespread, and they are actively transforming dental and craniofacial medicine. The introduction of artificial intelligence into prosthetic dentistry for the rehabilitation of patients with maxillofacial area injuries can enhance the accuracy of diagnosis and simplify treatment planning. Additionally, it will facilitate the development of a personalized approach to orthopedic rehabilitation planning through digital analysis of diagnostic data, enabling the determination of effective orthopedic interventions for each patient with tooth loss resulting from maxillofacial injuries. A personalized digital dental passport encoded using digital technologies can provide rehabilitation and manufacture of prostheses based on 3D-printed dental biomaterials. The paper discusses the use of 3D scanners and CAD/CAM technologies, which involve digital programs (Dentsply Sirona CEREC, 3Shape TRIOS, Exocad, Blue Sky Plan, Nobel Biocare, Mesh mixer, Dental Wings), to improve the accuracy of diagnosis, planning, and manufacturing of prostheses. Thus, the analysis of the possibilities of orthopedic diagnostic methods for patients who have lost their teeth due to injury has shown that artificial intelligence is expanding diagnostic and treatment capabilities. Thanks to various types of computed tomography, intraoral scanning, digital occlusiography, and modern digital programs and platforms, it is possible to develop individualized treatment plans, plan orthopedic rehabilitation more accurately, and increase its effectiveness. Therefore, the introduction of these technologies can help improve medical outcomes, increase patient satisfaction, and increase the efficiency of the healthcare system.